PRINCIPLES OF TRANSFER PRICE FORMATION IN THE MULTICOMPONENT ENTERPRISES - Stonciuviene, Neringa; Uzkuraite, Simona (European Scientific Journal, ESJ, 2015)
Transfer pricing is one of the characteristics and benefits of a decentralized company. Business companies usually opt for decentralization in order to abandon the principle of centralized management, enhance responsibility of the responsibility centres that usually perform the function of profit centres, as well as their interest in better corporate performance results. Several transfer pricing methods are discussed in scientific literature and applied to practice, such as market-based transfer price, cost-based transfer price, and negotiated transfer price methods. The paper presents the study that analyses the transfer pricing methods, identifies their benefits and weak aspects, and presents principles to be followed by the managers of responsibility centres and company when choosing the appropriate transfer pricing method. During consideration of the most appropriate transfer pricing method, the possibility for division to gain profit and receive compensation from the central management must be considered.